Keragaman Genetik Kultivar Padi Beras Hitam Lokal Berdasarkan Penanda Mikrosatelit - Kristamtini Kristamtini; Taryono Taryono; Panjisakti Basunanda; Rudi H. Murti (Jurnal AgroBiogen, 2014)
Indonesia has diverseaccessions of local black rice, which are important sourcesof germplasm. However, some of the local black ricecultivars have different names, leading a need to beidentified to determine their genetic diversity usingmolecular marker. This study aimed to identify geneticdiversity of eleven cultivars of local black rice, collection ofthe Assessment Institute for Agricultural Technology,Yogyakarta and compared them with two white ricevarieties using four microsatellite markers. Detection ofmicrosatellite alleles polymorphism was carried out byvisualization of PCR amplicons by electrophoresis onagarose gel. To estimate their genetic diversity, phylogenetictree and principal coordinate analysis were performed usingbinary data of SSR alleles. The results revealed that totalmarkers enabled to differentiate black rice cultivars asreflected by high value of polymorphic information content(PIC) mean (0.695). This value was consistent with the highgenetic diversity of black rice (genetic diversity index, h =0.283) in comparison with white rice cultivars (h = 0.020).The phylogenetic and main coordinate analyses suggestedthat black rice cultivars genetically differed from white rice.The local black rice cultivars were preferentially groupedbased on their genetic those were distributed in threecoordinates and did not represent their local geographicorigin. Genetic diversity analysis in this study will be usefulas an initial basis for proper identification and selection forappropriate parents to assist breeding program of black ricein Indonesia.